A Simple Model for Predicting Upwelling Status along Visakhapatnam Coast - K., Vijayakumaran (Fishery Technology, 2025)
The variations in water mass characteristics of temperature, salinity and density over 12 year period (1986-1997) from a near-shore station are presented to delineate the phenomenon of upwelling off Visakhapatnam. The spatial variation in the parameters during upwelling months for a limited period was examined to justify the selection of a near-shore station for predicting the status of upwelling. A simple model to predict upwelling status based on Knudsen’s hydrographic calculations and La Fond’s classification of water masses was constructed and the algorithm presented. The utility of the model is briefly mentioned.